PENGARUH BIAYA PRODUKSI DAN BIAYA PEMASARAN TERHADAP HASIL PENJUALAN PADA RUMAH MAKAN DI KECAMATAN KUTA SELATAN - Oktavia Magdalena; Made Christin Dwitrayani; Made Yudi Darmita (Universitas Triatma Mulya, 2022)
This research are focus to the product costs and marketing costs affects sales results from micro, small and medium enterprises in the field of feeding business specially in Bali. The type of data used is qualitative data on restaurants in South Kuta subdistrict, and quantitative data research by using survey method. Total of the population is 522 restaurants in South Kuta subdistrict and using purposive sampling to get 84 samples. Observation and questionnaires used to collect the primary and secondary data. The analytical tools used are data quality tests, classical assumption tests, multiple linear regression analysis, coefficient of determination tests, and hypothesy tests. The result of this research that product costs and marketing costs simultaneously influential to sales results on restaurants in South Kuta subdistrict. The first t tests results by looking to the significance value (0,003< 0,05) show that product costs positive effect to sales results on restaurants in South Kuta subdistrict. The second t tests results have significance value (0,000<0,05) show that marketing costs positive effect to sales results on restaurants in South Kuta subdistrict.